Using curricular spider web to explore a research facilitator’s and students’ experiences… - Khoza, Simon Bhekimuzi (South African Journal of Higher Education, 2016)
This article presents an interpretive case study of two groups of students and a facilitator, who were involved in the learning and teaching of a postgraduate research module. The module was face-to-face for a group of twenty four students and fourteen distance learning students. The facilitator had to use different e-resources to create an e-learning environment for the students to learn. Document/LMS analysis, semi-structured interviews/discussion and participant observations were used for data generation. Purposive sampling was used in selecting these two specific groups of research students and their facilitator. This article uses the term ‘e-learning signals’ to group every important element of e-learning environments. Twelve issues of learning are presented for discussing the important activities for learning framed by the curricular spider web. This article consequently recommends that facilitators and students should define, understand, and use or apply the e-learning environment in order to support learning.